The interplay of ideal L2 self, L2 investment and L2 identity of EFL learners in higher education: A systematic review from 2014 to 2024 - Yao Zhou; Supyan Hussin; Azlina Binti Abdul Aziz (Environment and Social Psychology, 2025)
This systematic review examines the dynamic interplay among ideal L2 self, L2 investment, and L2 identity in university-level EFL contexts by synthesizing 26 empirical studies (2014-2024). Addressing key gaps in current research, it integrates psychological and sociological perspectives while expanding beyond dominant East Asian contexts to include underrepresented regions. The findings reveal that the ideal L2 self serves as a primary motivational driver, particularly when supported by digital affordances and positive emotional experiences, while pedagogical interventions that facilitate vision-building and identity reflection create reinforcing cycles of motivation and investment. However, structural barriers such as socioeconomic disparities significantly constrain these dynamics for marginalized learners. The review makes three key contributions: first, it develops an integrated framework connecting agency and structure in L2 motivation research; second, it demonstrates the value of mixed-methods approaches for capturing temporal and contextual dimensions; and third, it provides practical insights for designing inclusive pedagogies that address systemic barriers. By elucidating the interdependent relationships among ideal L2 self as future self-guides, strategic investment, and identity development, this review advances understanding of L2 learning as both a cognitive and sociocultural process, offering valuable guidance for researchers, educators, and policymakers seeking to promote equitable learning opportunities in diverse EFL contexts and provides a comprehensive framework for understanding language learners’ motivational trajectories, with implications for research, teaching practice, and policy development in global higher education settings.